Analisis Peran Hukum dalam Penanggulangan Tindak Kekerasan dalam Rumah Tangga - Roosnelly R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Domestic Violence (Kekerasan Dalam Rumah Tangga/KDRT) is a form of human rights violation and a crime against human dignity, with women and children being the majority of victims. This study aims to analyze the role of law in both preventive and repressive dimensions, as well as to identify obstacles in law enforcement efforts to address domestic violence in Indonesia. This research employs a normative legal research method using a statutory approach and a conceptual approach. The results indicate that the enactment of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) provides a strong legal foundation through protection against physical, psychological, sexual violence, and household neglect. However, the effectiveness of law enforcement remains hindered by patriarchal culture, social stigma that considers domestic violence as a private or domestic matter, limited understanding among law enforcement officials, and inadequate victim protection facilities. Therefore, synergy between public legal education, strengthening the capacity of law enforcement institutions, and optimizing victim protection agencies is required to maximize the role of law in preventing and addressing domestic violence.